The Development of Integrated Science E-Module on the Theme of Loving God’s Earth Integrated with the Qur’an and Hadith in Madrasah Tsanawiyah: Pengembangan E-modul IPA Terpadu Tema Mencintai Bumi Allah Terintegrasi Al-Qur'an dan Hadis di Madrasah Tsanawiyah - Nilam Sari (Pendidikan IPA, FMIPA, UNP, 2023)
Developing moral values to nature through Integrated Science lessons is a strategic tool, especially in Madrasah Tsanawiyah (MTs) where learning moral values to nature in Integrated Science learning can be based on the Qur'an and Hadith. The Earth's Layer and its Development is one of the science learning materials that can be integrated with the Qur'an and Hadith, through integrated teaching materials that use themes and follow the development of the current digital era, where teaching materials will be easier to use and efficient if they are digital. This study aims to produce teaching material products in the form of integrated science E-Modules with the theme of Loving Allah's Earth integrated with the Qur'an and Hadith in Madrasah Tsanawiyah which are valid and practical. The type of research used is Research and Development (R&D) with product development using three stages of the 4-D model, namely define, design, and development. The results of data analysis obtained from the validity test obtained an average value of 0.88 with a very valid category, and the results of the practicality test obtained an average value of 0.99 by teachers and an average value of 0.88 by students with a very practical category.